2003
DOI: 10.1046/j.1464-410x.2003.04232.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of familial prostate cancer risk

Abstract: calculating the weighted average of the log relative risk (RR) estimates from studies. RESULTSThe pooled RR (95% confidence interval) in first-degree relatives was 2.5 (2.2-2.8). There was evidence that this was highest in relatives of cases diagnosed before age 60 years and that RRs declined with age. The risk for the few men with two affected relatives was increased 3.5-fold (2.6-4.8). RRs to sons of cases appeared to be lower than in brothers; a complete explanation of this observation is uncertain. CONCLUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
1
13

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(183 citation statements)
references
References 50 publications
(105 reference statements)
8
161
1
13
Order By: Relevance
“…Several 2,21,30,35 but not all, 22 studies have found that a history of prostate cancer in a sibling confers greater risk than that of paternal history, which would be consistent with the additional contribution to risk of a shared environment in childhood and adolescence. We observed a somewhat stronger association with paternal history, although the number of cases was small, and the confidence intervals for paternal versus sibling history were not mutually exclusive.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Several 2,21,30,35 but not all, 22 studies have found that a history of prostate cancer in a sibling confers greater risk than that of paternal history, which would be consistent with the additional contribution to risk of a shared environment in childhood and adolescence. We observed a somewhat stronger association with paternal history, although the number of cases was small, and the confidence intervals for paternal versus sibling history were not mutually exclusive.…”
Section: Discussionmentioning
confidence: 73%
“…A recent meta-analysis estimated that a family history of prostate cancer in first-degree relatives was associated with a relative risk of 2.5 [3.5 for risk of early onset (<60 years old) disease]. 2 However, most existing studies are limited to retrospective case-control studies [3][4][5][6][7] and some existing cohort studies are based on family history probands. [8][9][10] Additionally, 2 prospective studies reported that associations between body mass index and prostate cancer were more pronounced among men with a positive family history, 11,12 but data evaluating interactions with other important prostate cancer risk factors are limited.…”
mentioning
confidence: 99%
“…Ample epidemiologic evidence suggests that prostate cancer has both a familial and genetic component (1). In one meta-analysis, the pooled risk of prostate cancer was higher in men who had a father or brother affected by prostate cancer, compared to a control population with no affected relatives (RR 2.5, 95%CI 2.2-2.8) (14). Another meta-analysis showed an increased risk of prostate cancer for any affected family member (RR 2.04, 95%CI 1.64-2.55), a higher risk for disease for affected fi rst-degree relatives (RR 2.24, 95%CI 2.08-2.41), and an elevated risk of cancer in affected second-degree relatives (RR 1.91, 95%CI 1.58-2.30) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Os 22 , mas nenhum estudo até a presente data foi conclusivo [8][9][10][22][23][24] . O risco de desenvolvimento de doença neoplásica maligna associada à exposição ao OEt não pode, até a presente data, ser confirmado.…”
Section: Relato De Caso Médico-pericialunclassified
“…Em relação à etnia, os afroamericanos têm maior risco de desenvolver a doença, entre dez a quarenta vezes mais que os asiáticos 6,7 . Parentes de primeiro grau de sujeitos com CP apresentam de duas a três vezes mais chance de ter a doença, quando comparados a homens na população geral 8,9 . A dieta altamente calórica e os hormônios masculinos também são fatores de risco 10,11 .…”
Section: Introdução Ounclassified